GitOps: A Path to More Self-Service IT. - LIMONCELLI, THOMAS A. (Communications of the ACM, 2018)
The article discusses GitOps workflow which empowers users to perform their own information technology (IT) operations through pull requests (PRs). Topics include the ability of GitOps to lower the bar for creating self-service versions of common IT and encourage better testing, reduced wait times, and increased time for creating and maintaining automation.